Factors Affecting Indonesian Sharia Commercial Bank Financial Performance - Hartikayanti , Heni Nurani; Siregar, Ifan Wicaksana (International Journal of Psychosocial Rehabilitation, 2020)
Purpose: This research aims at analyzing the effect of Fund from Third Party (FTP), Non-Performing Financing (NPF), and Financing to Deposit Ratio (FDR) both partially and simultaneously on Bank Profitability of the Indonesia Sharia Commercial Banks during the 2013-2017 periods. Design/methodology/approach: This research employs quantitative method by involving Sharia Commercial Banks listed on the Financial Services Authority of Indonesia (OJK, Otoritas Jasa Keuangan) as the population. The sample was selected using purposive sampling method resulted in 11 banks. The data were analyzed using multiple regression analysis with a 5% level of significance with a classical assumption test. Findings: The findings revealed that (1) Partially FTP and FDR had an insignificant positive influence on bank profitability, and NPF had a significant negative influence on bank profitability in Sharia Commercial Banks listed on OJK and (2) FTP, NPF, and FDR simultaneously had a significant influence on bank profitability in Sharia Commercial Banks listed on OJK. Research limitations/implications: The factors studied are limited to internal financial factors Practical implications: Bank managers should not use third party funds for investment assets or other expenses. Originality/value: Financial performance of Indonesian Islamic banks